PREDICTORS OF MAJOR BLEEDING AMONG ATRIAL FIBRILLATION PATIENTS ON WARFARIN - M MATALQAH, LAILA; YEHYA, ALAA; AL-TAANI, GHAITH M (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Bleeding is the most serious complication associated with anticoagulation therapy. The purpose of this study was to estimate the frequency of major bleeding related to warfarin and to identify its predictors in patients with atrial fibrillation (AF). Methods: Patients with AF treated with warfarin at Penang General Hospital in Malaysia were identified according to the international classification of disease, Ninth Revision, Clinical Modification (ICD-9). The medical reports of 1611 patients were reviewed, bleeding events were set as primary end point which were identified in 313 patients. Demographic and clinical data were retrieved and warfarin therapy-related parameters including dose, therapy duration, and prothrombin time-international normalized ratio (PT-INR) were recorded and analyzed using descriptive statistics. Results: Of the 313 patients, 28 patients with major bleeding events were identified. Gastrointestinal bleeding was the major type of bleeding, which accounts for 68% (n = 17) of the cases. The frequency of major bleeding events among all AF patients was 1.7%. High PT-INR value was found in 96.3% (n = 28) of the patients, thereby making it the primary predictor of bleeding events. Other predictors including, advanced age, other comorbidities such as hypertension and multiple anticoagulation therapy were also observed to be significant. Conclusion: Lower doses of warfarin are recommended to achieve target PT-INR range similar to that reported previously for Asian populations. A regular clinical review for bleeding predictors is essential for maximizing the time spent by the patient taking warfarin in the optimal therapeutic range and for making recommended therapy adjustment.